Avaliação da rotulagem nutricional obrigatória de preparações culinárias paraenses comercializadas em supermercados de Belém do Pará - RAMOS, Danilo Silva (2023)
The labels are a strategic tool for maintaining consumer health and safety, representing a space for communication between producers and consumers regarding their quality and adequacy to the requirements of the Consumer Protection and Defense Code. Objective: To evaluate the mandatory nutritional labeling of ingredients used in paraense culinary preparations derived from Cassava (Manihot esculenta Crantz). Material and methods: The preparations available in the main supermarket chains in the city of Belém were researched and three preparations were found, each of maniçoba, duck in tucupi and turkey in tucupi, and compared with current legislation in RDC nº 259/2002, RDC nº 276/2005, RDC nº 360/2003, Law nº 10,674/2003, Law nº 8,078/1990 and Law nº 6,437/1977. Results: The three labels do not comply with the legislation. They have difficulties in reading batch data, expiration date and date of manufacture, in addition to the omission of information on the ingredients used and the manufacturer's address, contrary to what was established in RDC nº 259/2002. Furthermore, the calculations of the daily intake values (VD%) of the preparations are based on a 2500 Kcal diet with a deviation of up to 30% of the calculations, contrary to RDC nº 360/2003 which establishes 2.000 Kcal or 8.400 KJ with a maximum deviation 20%. In this way, all the values of VD% were underestimated, exceeding that recommended by the world health organization for a healthy diet, being a risk factor for the development of chronic non communicable diseases.